Different Associations Between CDKAL1 Variants and Type 2 Diabetes Mellitus Susceptibility: A Meta-analysis - Zeng, Qiaoli; Zou, Dehua; Gu, Shanshan; Han, Fengqiong; Cao, Shilin; Wei, Yue; Guo, Runmin (Frontiers in Genetics, 2022)
Background: CDK5 regulatory subunit associated protein 1 like 1 (CDKAL1) is a major pathogenesis-related protein for type 2 diabetes mellitus (T2DM). Recently, some studies have investigated the association of CDKAL1 susceptibility variants, including rs4712523, rs4712524, and rs9460546, with T2DM. However, the results were inconsistent. This study aimed to evaluate the association of CDKAL1 variants and T2DM patients. Methods: A comprehensive meta-analysis was performed to assess the association between CDKAL1 SNPs and T2DM among dominant, recessive, additive, and allele models. Results: We investigated these 3 CDKAL1 variants to identify T2DM risk. Our findings were as follows: rs4712523 was associated with an increased risk of T2DM for the allele model (G vs. A: OR=1.172; 95% CI: 1.103–1.244; P＜0.001) and dominant model (GG +AG vs. AA: OR = 1.464; 95% CI: 1.073–1.996; P = 0.016); rs4712524 was significantly associated with an increased risk of T2DM for the allele model (G vs. A: OR=1.146; 95% CI: 1.056–1.245; P=0.001), additive model (GG vs. AA: OR=1.455; 95% CI: 1.265–1.673; P＜0.001) recessive model (GG vs. AA + AG: OR=1.343; 95% CI: 1.187–1.518; P＜0.001) and dominant model (GG +AG vs. AA: OR = 1.221; 95% CI: 1.155–1.292; P＜0.001); and rs9460546 was associated with an increased risk of T2DM for the allele model (G vs. T: OR=1.215; 95% CI: 1.167–1.264; P=0.023). The same results were found in the East Asian subgroup for the allele model. Conclusions: Our findings suggest that CDKAL1 polymorphisms (rs4712523, rs4712524, and rs9460546) are significantly associated with T2DM.